Artifact Reduction in Simultaneous EEG-fMRI: A Systematic Review of Methods and Contemporary Usage - Bullock, Madeleine; Jackson, Graeme D.; Abbott, David F. (Frontiers in Neurology, 2021)
Simultaneous EEG-fMRI is a technique that combines temporal (largely from EEG) and spatial (largely from fMRI) indicators of brain dynamics. It is useful for understanding neuronal activity during many different event types, including spontaneous epileptic discharges, the activity of sleep stages, and activity evoked by external stimuli and decision-making tasks. However, EEG recorded during fMRI is subject to imaging, pulse, environment and motion artefact, causing noise many times greater than the neuronal signals of interest. Therefore, artefact removal methods are essential to ensure that artefacts are accurately removed, and EEG of interest is retained. This paper presents a systematic review of methods for artefact reduction in simultaneous EEG-fMRI from literature published since 1998, and an additional systematic review of EEG-fMRI studies published since 2016. The aim of the first review is to distil the literature into clear guidelines for use of simultaneous EEG-fMRI artefact reduction methods, and the aim of the second review is to determine the prevalence of artefact reduction method use in contemporary studies. We find that there are many published artefact reduction techniques available, including hardware, model based, and data driven methods, but there are few studies published that adequately compare these methods. In contrast, recent EEG-fMRI studies show overwhelming use of just one or two artefact reduction methods, based on literature published fifteen to twenty years ago, with newer methods rarely gaining use outside the group that developed them. Surprisingly, almost 15% of EEG-fMRI studies published since 2016 fail to adequately describe the methods of artefact reduction utilised. We recommend minimum standards for reporting artefact reduction techniques in simultaneous EEG-fMRI studies and suggest that more needs to be done to make new artefact reduction techniques more accessible for the researchers and clinicians using simultaneous EEG-fMRI.